Determinants of household credit behavior of low-income households in Sri Lanka - Dharmadasa, Champika; Gunatilake, MM (Asian Economic and Financial Review, 2023)
The paper aims to achieve three objectives in relation to household borrowing behavior among low-income households in Sri Lanka. First, it attempts to understand the patterns of savings and credit behavior of households. Second, it identifies the underlying reasons for the credit demand of households. Third, it investigates the relative significance of demographic and other socioeconomic factors that influence the reasons for households’ credit demand. Primary data collected from 1,500 household units were utilized for the analysis. Thematic and multinominal logistic regression analyses were used to achieve objectives. The thematic analysis identified 533 household units in debt and has revealed eight reasons behind households’ borrowing decisions, with borrowing for housing renovations, investing and consumption being the top three reasons. The results of the multinominal regression analysis revealed that having children is the most influential demographic factor that lies behind most reasons. The paper concludes that only a few households have borrowing habits, and their borrowing purposes vary. Most are not used for productive investments, and having young dependents induces household borrowing decisions. Based on the outcome, the study suggests strengthening social assistance for households with young dependents to protect low-income families from indebtedness.